Psychological Characteristics of the Development of Analytical Thinking in Adolescents - Namoz ugli, Ashrapov Nodirbek (Jurnal Psikologi, 2025)
This study aims to investigate the psychological characteristics that influence the development of analytical thinking during adolescence. Specifically, it examines how emotional stability, self-awareness, intellectual engagement, and educational environments contribute to the growth of adolescents’ analytical thinking. The research employs a mixed-methods approach: quantitative methods include surveys, intelligence tests, and psychological scales, while qualitative data are collected through observations, interviews, and focus group discussions. Statistical analysis was conducted on factors such as emotional resilience, critical thinking skills, and the use of interactive methods in classrooms. The results reveal that emotional stability and self-awareness have significant impacts on adolescents’ analytical abilities. Moreover, intellectual activity, social support, and the regular use of interactive teaching methods were found to strongly enhance cognitive and analytical development. The findings suggest that a comprehensive and individualized pedagogical strategy—one that integrates psychological support, digital tools, and collaborative learning—is essential for fostering analytical thinking in adolescents.